Angelization and demonization of the victim and the hero in Western literature of the nineteenth century: from John Milton to Arthur Rimbaud - Жужгина-Аллахвердян, Тамара Николаевна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The main subjects of the research are the biblical archetypes and its functioning in the poetry of Milton, Maturin, Byron, Vigny, Baudelaire, A. Rimbaud. This article provides an analysis of the mythopoetical, ethical and several psychological aspects and motives of angelization and demonization of the victim and the hero, the transformation and modification of the old Testament themes, the actualization of the biblical symbols of human feelings and contradictions of earthly existence in romanticism.